2012
DOI: 10.12799/jkachn.2012.23.2.222
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Senior Simulation Programs on Elderly Care Facilities Employees' Attitudes for Elderly Care, Understanding of the Aged, Job Satisfaction, and Job Performance

Abstract: Purpose: This research is to understand the effects of senior simulation on employees of elderly care facilities and utilize it in their job training. Methods: This research is a nonequivalence control group pre-to-post quasiexperiment research. 18 employees who have experienced senior simulation are set as test group and 18 other employees who have not experienced senior simulation are set as control group. Results: The hypothesis that 'the test group which has experienced senior simulation will show a positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…A higher total score indicates a more positive attitude toward the elderly. In terms of the reliability of the scale, Cronbach’s a was 0.92 in Joung & Hyun’s research [ 22 ] and 0.93 in the present study.…”
Section: Methodssupporting
confidence: 46%
See 2 more Smart Citations
“…A higher total score indicates a more positive attitude toward the elderly. In terms of the reliability of the scale, Cronbach’s a was 0.92 in Joung & Hyun’s research [ 22 ] and 0.93 in the present study.…”
Section: Methodssupporting
confidence: 46%
“…This is a similar level of improvement as was reported in Joung and Hyun’s study [ 21 ] with elderly care facility employees, which found an improvement of 2.61 (−1.4) from the pre-mean (SD) of 69.11 (6.12) to the post-mean (SD) of 71.72 (4.72). In Joung and Hyun’s study [ 22 ], the control group showed a decrease of 3.45 (−0.13) points when comparing the pre- and post-mean (SD) scores of their attitudes toward caring for the elderly. It is thought that the senior simulation program of this previous study and the experiential learning of the S-PBL as interventions of the present study can contribute to broadening students’ perspectives toward caring for elderly patients and their understanding of patient care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Care attitudes toward older adults ( 39 ) was used to assess caregivers’ care attitude, and were based on the Youth’s Attitudes Toward the Elderly ( 40 ) and the Maxwell-Sullivan Attitudes Scale Toward the Geriatric Patient ( 41 ). Care attitudes for older adults were assessed using a total of 17 items.…”
Section: Methodsmentioning
confidence: 99%